The Correlation Between Students’ Vocabulary Mastery and Listening Achievement at 10th A Grade of Smks Keluarga Bunda Jambi - Rahmah; Yulia Wiji Astika; Siti Rahmiati; Teta Wismar (Journal of Research in Business, Economics, and Education, 2021)
Language is the basic skills are needed for real communication among people. Vocabulary and listening is one of the problems confronted by English language learners . SMKS Kesehatan Keluarga Bunda Jambi is one of Islamic boarding school that have problem in English lesson. The students have low motivation for study English, especially in vocabulary and listening. Based on explanation above, it is interested to conduct the research with entitled “The Correlation Between Students’ Vocabulary Mastery and Listening Achievement at 10th A Grade of SMKS Keluarga Bunda Jambi. Research design was use correlation research design with quantitative method. The population of the research was all students of 10th grade students’ at SMKS Kesehatan Keluarga Bunda Jambi, Academic Year 2021. The sample in this research was 26 students from Nursing Class and Pharmacy Class. There is no significant correlation of students’ vocabulary mastery and listening achievement at 10th A grade students of SMKS Keluarga Bunda Jambi, Academic Year 2021. It can be proved with the result is 0.670. The correlation is positive and can be categorized as substantial correlation.